Learning civic education on students' legal awareness - Tjeppy, Tjeppy (Universitas Negeri Yogyakarta, 2021)
Increasing legal awareness must start from education. A good education will produce humans who are responsible, tolerant, and care for the environment. Legal awareness among students is essential. Students are the nation's next generation. High legal awareness among lessons can provide comfort and discipline, especially in schools and, in general, in the community. This study aimed to analyze civic education learning's effectiveness on legal awareness of class X students at SMAN 1 Ciranjang, Cianjur regency. The method used is a quantitative method with 60 students and sampling using purposive sampling with a sample size of 60 students. The descriptive analysis results show that the class X student civic education learning at SMAN 1 Ciranjang is in the high category with an average score of 80.60 of the ideal score of 100. The legal awareness of class X students at SMAN 1 Ciranjang is in the high sort with an average score of 80, 57 out of the ideal score of 100. The inferential analysis results show a significant influence between civic education learning on legal awareness in class X students at SMAN 1 Ciranjang. The results showed that high school students' common understanding was implemented on the students' values regarding the level of obedience to the existing laws (school rules). Students carry out legal awareness among students towards their high understanding of the law for students that can result in obeying the rules that apply in school. On the other hand, low awareness among students will violate the regulations that apply in schools.